2003
DOI: 10.1177/0022487102250287
|View full text |Cite
|
Sign up to set email alerts
|

The Effects Of Collaborative Action Research On Preservice And Experienced Teacher Partners In Professional Development Schools

Abstract: Abstract:This study describes the perspectives of five pairs of preservice teachers and their experienced mentor teachers who engaged collaboratively in planning, implementing, and evaluating action research projects during a semester-long internship experience in their professional development school sites. The views of novice and experienced teachers about the costs and benefits of doing collaborative action research are presented, and the authors elaborate on the development of the mentor/mentee relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
95
1
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(106 citation statements)
references
References 18 publications
4
95
1
6
Order By: Relevance
“…To characterize further the present report of AR, its participatory dimension must also be underlined (Levin and Rock 2003;McIntyre et al 2007;Mitchell, Reilly, and Logue 2009). Against the negative trend emphasized by Van Sluys (2010, 141), my students and I were actually both the subjects and the objects of our research; both researchers and researched subjects.…”
Section: Introduction: Meta-action Researchmentioning
confidence: 85%
“…To characterize further the present report of AR, its participatory dimension must also be underlined (Levin and Rock 2003;McIntyre et al 2007;Mitchell, Reilly, and Logue 2009). Against the negative trend emphasized by Van Sluys (2010, 141), my students and I were actually both the subjects and the objects of our research; both researchers and researched subjects.…”
Section: Introduction: Meta-action Researchmentioning
confidence: 85%
“…The programs at OISE and the University of Calgary are examples of the later, while the program at the University of Winnipeg uses the former approach. Action research is seen as a critical mechanism for fostering the beginning professional learning experiences of teacher candidates, and as a modus operandi of effective teachers (Levin & Rock, 2003). Action research fosters collaborative, reflective and in-situ experiences, which appear to be necessary conditions for exploring the complexities of teaching (Levin & Rock, 2003).…”
Section: Action Researchmentioning
confidence: 99%
“…Ferrance (2000:1) also adds that action research is "a collaborative activity among colleagues searching for solutions to everyday, real problems experienced in schools, or looking for ways to improve instruction and student achievements". Moreover, it has been suggested that one way to improve teaching and learning in schools or in any other educational context is to involve teachers in conducting research in their own classroom (Levin and Rock, 2003).…”
Section: Action Researchmentioning
confidence: 99%